Socioecology of the Australian Tree Skink (Egernia striolata) - Riley, Julia L.; Noble, Daniel W. A.; Stow, Adam J.; Bolton, Peri E.; While, Geoffrey M.; Dennison, Siobhan; Byrne, Richard W.; Whiting, Martin J. (Frontiers in Ecology and Evolution, 2021)
There is great diversity in social behavior across the animal kingdom. Understanding the factors responsible for this diversity can help inform theory about how sociality evolves and is maintained. The Australian Tree Skink (Egernia striolata) exhibits inter- and intra-population variability in sociality and is therefore a good system for informing models of social evolution. Here, we conducted a multi-year study of a Tree Skink population to describe intra-population variation in the social organization and mating system of this population. Skinks aggregated in small groups of 2 to 5 individuals, and these aggregations were typically associated with shared shelter sites (crevices and hollows within rocks and trees). Aggregations were typically made up of one or more adult females and, often, one male and/or juvenile(s). Social network and spatial overlap analyses showed that social associations were strongly biased towards kin. Tree skinks also exhibited high site fidelity regardless of age or sex. There were high levels of genetic monogamy observed with most females (87%) and males (68%) only breeding with a single partner. Our results indicate that Tree Skinks reside in small family groups and are monogamous, which corresponds with existing research across populations. Similar to previous work, our study area, consisted of discrete habitat patches (i.e., rock outcrops, trees, or both), which likely limits offspring dispersal and promotes social tolerance between parents and their offspring. Our study clearly demonstrates that there is intra-population variability in Tree Skink social behavior, but it also provides evidence that there is a high degree of inter-population consistency in sociality across their geographic range. We also highlight promising possible avenues for future research, specifically discussing the importance of studying the nature and extent of Tree Skink parental care and quantifying the fitness outcomes of kin-based sociality in this species, which are topics that will further our understanding of the mechanisms underlying variation in vertebrate social behavior.